Yafa Shanneik, Chris Heinhold y Zahra Ali (dirs.) (2017). Mapping Shia Muslim communities in Europe. Local and transnational dimensions, número especial del Journal of Muslims in Europe, 6(2). - Sylvie Taussig (El Colegio de México, A.C., 2018)
Yafa Shanneik, Chris Heinhold y Zahra Ali (dirs.) (2017). Mapping Shia Muslim communities in Europe. Local and transnational dimensions, número especial del Journal of Muslims in Europe, 6(2).